Calcium dynamics of plasmodium berghei sporozoite motility - Carey, Allison F.; Singer, Mirko; Bargieri, Daniel; Thiberge, Sabine; Frischknecht, Friedrich; Ménard, Robert; Amino, Rogerio (Cellular microbiology, 2014)
Calcium is a key signalling molecule in apicomplexan parasites and plays an important role in diverse processes including gliding motility. Gliding is essential for the malaria parasite to migrate from the skin to the liver as well as to invade host tissues and cells. Here we investigated the dynamics of intracellular Ca2+ in the motility of Plasmodium berghei sporozoites by live imaging and flow cytometry. We found that cytosolic levels of Ca2+ increase when sporozoites are activated in suspension, which is sufficient to induce the secretion of integrin-like adhesins that are essential for gliding motility. By increasing intracellular Ca2+ levels artificially with an ionophore, these adhesins are secreted onto the sporozoite surface, however, the parasite is not capable of gliding. A second level of Ca2+ modulation was observed during attachment to and detachment from a solid substrate, leading to a further increase or a decrease in the cytoplasmic levels of Ca2+ respectively. We also observed oscillations in the intracellular Ca2+ level during gliding. Finally, an intracellular Ca2+ chelator, an inhibitor of phosphoinositide-specific phospholipase C (PI-PLC), and an inhibitor of the inositol triphosphate (IP3) receptor blocked the rise in intracellular Ca2+, adhesin secretion, and motility of activated sporozoites, indicating that intracellular stores supply Ca2+ during sporozoite gliding. Our study indicates that a rise in intracellular Ca2+ is necessary but not sufficient to activate gliding, that Ca2+ levels are modulated in several ways during motility, and that a PI-PLC/IP3 pathway regulates Ca2+ release during the process of sporozoite locomotion.
Gesehen am 10.09.2020